THE PHISICAL THERAPY PART IN SCHOLAR INCLUSIVE PROCESS (Fiep Bulletin - online, 2014)
In the last few years, some separeted acts from parents and educator has promoted and improved the scholar inclusive process, aiming at ranson the human respect and dignity, on purpose to provide full development and the access to all society resources. The objective of this project aims to investigate the phisical therapy contributions to this process through documentary analisys. The results were: from june to december of 2005 seven schools were visited to indentify, evaluate and lead those students with some learning disturbs to Univali's Phisical Therapy School Center, such as to orientate parents, teachers and monitors; in February of 2006 at Arnaldo Brandão Municipal School, were executated relaxing and streching exercices and postural valuation in 1ª to 4ª greads studants, in those were detected several posture disturbs specialy intern rotation of the shoulder; in Agost of 2006 were included on phisical therapy aproach the Pedagogic Living Experiences Laboratory, with relaxing and streching exercices on the swimming pool, and pedagogic activities with hiperactive students. After this research the fisical therapy was included in health promotion, and the interdisciplinarity relation between the professionals were fortifyed.
Keywords: Phisical therapy; phisical deficiency; scholar inclusion